2021
DOI: 10.9770/jesi.2021.9.2(28)
|View full text |Cite
|
Sign up to set email alerts
|

Laffer curve - a comparative study across the V4 (Visegrad) countries

Abstract: The essence of the Laffer curve is simple -it represents the relationship between the tax rate imposed by a government and the tax revenues. Tax revenues are the product of the tax rate and the tax base. For this article and based on the theory that underpins the Laffer curve, the application thereof is generalized, and the economic growth rate adopted instead of tax revenues. The purpose of this article is, on the basis of the theory that underpins the Laffer curve, to determine the optimal tax rate in the V4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Nearly all goods and services are subjected to a certain tax rate to generate this tax revenue. One type of curve that shows the relationship between the tax imposed by the government and tax revenues collected is the Laffer Curve, presented by the economist Arthur Laffer (Wang et al, 2021), as shown in Figure 3. The Laffer effect has been discussed in the context of labor supply, whether a tax cut on wages would lead people to work more (Özçam, 2014).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Nearly all goods and services are subjected to a certain tax rate to generate this tax revenue. One type of curve that shows the relationship between the tax imposed by the government and tax revenues collected is the Laffer Curve, presented by the economist Arthur Laffer (Wang et al, 2021), as shown in Figure 3. The Laffer effect has been discussed in the context of labor supply, whether a tax cut on wages would lead people to work more (Özçam, 2014).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…At the microeconomics level, tax revenues can affect people's daily lives by influencing their choices and decisions, such as savings and consumption. Whereas, at the macroeconomics level, tax revenues can affect a country's economic growth, investment models as well as allocation of resources (Wang et al, 2021). Wang et al (2021) conducted research on the V4 (Visegrad) countries including Poland, the Czech Republic, Slovakia, and Hungary, to examine the optimal tax rate in these countries.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, additional empirical research has been conducted regarding the Laffer curve. This is illustrated in the following three articles: Wang et al [54] investigated the optimal tax rate in the Visegrad Group (V4 countries), with data collected from 1995 to 2017. According to the research results, the Laffer curve reflects the general situation in those countries.…”
Section: The Relationship Between the Odd S-shaped Labor Supply And T...mentioning
confidence: 99%
“…A. Smith wrote about the danger of excessive tax burden back in the 18 th century, noting that an excessive tax burden can reduce or even destroy the funds that would enable them (people) to make these payments (taxes) with greater ease, and the ruin of companies due to excessive taxes leads to increased unemployment, which also makes it impossible to collect any tax money from the ruined, while their business development in more favourable conditions could bring its benefits for the economy of the country, including, in the form of the tax revenue. 235 Modern macroeconomic theory deals with this problem using the example of the Laffer curve (graphically depicts the dependence of tax collections on tax rates) and the tax multiplier (shows that reducing the tax burden frees up additional funds from taxpayers, which are directed to consumption or investment, which stimulates economic development and leads to its growth).…”
Section: Approaches For Analysing Taxes and The Tax Systemmentioning
confidence: 99%